Pangeo Forge: Crowdsourcing Analysis-Ready, Cloud Optimized Data Production - Stern, Charles; Abernathey, Ryan; Hamman, Joseph; Wegener, Rachel; Lepore, Chiara; Harkins, Sean; Merose, Alexander (Frontiers in Climate, 2022)
Pangeo Forge is a new community-driven platform that accelerates science by providing high-level recipe frameworks alongside cloud compute infrastructure for extracting data from provider archives, transforming it into analysis-ready, cloud-optimized (ARCO) data stores, and providing a human- and machine-readable catalog for browsing and loading. In abstracting the scientific domain logic of data recipes from cloud infrastructure concerns, Pangeo Forge aims to open a door for a broader community of scientists to participate in ARCO data production. A wholly open-source platform composed of multiple modular components, Pangeo Forge presents a foundation for the practice of reproducible, cloud-native, big-data ocean, weather, and climate science without relying on proprietary or cloud-vendor-specific tooling.